2014
DOI: 10.1099/mic.0.081166-0
|View full text |Cite
|
Sign up to set email alerts
|

The lack of OmpF, but not OmpC, contributes to increased antibiotic resistance in Serratia marcescens

Abstract: The environmental organism Serratia marcescens is one of the primary causes of numerous nosocomial outbreaks and opportunistic infections. Multi-drug resistance is now a common feature among S. marcescens clinical isolates, complicating the efficacy of treatment. Recent reports have attributed antibiotic resistance to altered porin expression as well as perturbation of the intrinsic AmpC beta-lactamase production pathway. In this study, we aimed to genetically correlate the absence of OmpF and OmpC classical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 41 publications
(58 reference statements)
2
26
0
Order By: Relevance
“…Complemented strain represented an 8-fold decrease in MIC values of imipenem and a 128-fold decrease of cephalosporins and meropenem MIC values. Another project emphasizing key role of OmpF protein was published by Moya-Torres et al (2014). Authors performed molecular characterization of permeability disorders in Serratia marcescens , and proved that OmpF protein was the most important factor contributing to changes in MIC values of β-lactams.…”
Section: Discussionmentioning
confidence: 99%
“…Complemented strain represented an 8-fold decrease in MIC values of imipenem and a 128-fold decrease of cephalosporins and meropenem MIC values. Another project emphasizing key role of OmpF protein was published by Moya-Torres et al (2014). Authors performed molecular characterization of permeability disorders in Serratia marcescens , and proved that OmpF protein was the most important factor contributing to changes in MIC values of β-lactams.…”
Section: Discussionmentioning
confidence: 99%
“…The species has the ability to infect plants, invertebrates, and vertebrates (1). Human infection, generally found in children and the immunocompromised, may include a variety of organ systems and is often resistant to common antibiotics (2, 3). The type strain sequenced here is used in many research and diagnostic applications as a control strain.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Choi and Lee (2019) demonstrated that the OmpF-defective E. coli mutants showed increased resistance to several β-lactam antibiotics, such as ampicillin, cefalotin, cefoxitin, ceftazidime, aztreonam, and imipenem [47]. The absence of OmpF classical porin resulted in a significant increase in β-lactam resistance, including ampicillin and cefoxitin [51]. Our findings corroborate previous reports that the MIC against several β-lactam antibiotics was decreased or increased in single isogenic β-lactamase or porin mutants, respectively (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…OmpC and OmpF are considered as the leading transport porins that assist penetration of most β-lactam antibiotics [47,[51][52][53], and both porins are known to be major protein components of E. coli OMVs [54]. Diffusion rates through these channels differ according to a substance's molecular weight and electrical charge [48,55].…”
Section: Discussionmentioning
confidence: 99%